2019
DOI: 10.1051/0004-6361/201935821
|View full text |Cite
|
Sign up to set email alerts
|

Systematic search for stellar pulsators in the eclipsing binaries observed byKepler

Abstract: Eclipsing binaries (EBs) are unique targets for measuring precise stellar properties and constrain stellar evolution models. In particular, it is possible to measure at the percent level masses and radii of both components of a double-lined spectroscopic EB. Since the advent of high-precision photometric space missions (MOST, CoRoT, Kepler, BRITE, TESS), the use of stellar pulsation properties to infer stellar interiors and dynamics constitutes a revolution for low-mass star studies. The Kepler mission has led… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 132 publications
0
46
0
Order By: Relevance
“…This problem of why some stars pulsate and others do not is not understood for close binary stars (Gaulme & Guzik 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem of why some stars pulsate and others do not is not understood for close binary stars (Gaulme & Guzik 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hence we have been searching for stars with their pulsation axis aligned with the tidal axis for over 40 years, since the discovery of oblique pulsation. Gaulme & Guzik (2019) conducted the first systematic survey of pulsating stars in eclipsing binaries in the Kepler eclipsing binary catalogue, which includes stars with orbital periods as short as 0.05 d. They found 13 systems with periods less than 0.5 d that show γ Dor or δ Sct pulsations, although they could not rule out false positives, e.g., potential third components, or background contamination. Interestingly, they could not come to a conclusion about whether being in a close binary suppresses pulsation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We developed an automatic pipeline -the Data Inspection Tool, hereafter DIT -to analyze the whole sample, which cleans the light curves and extracts the properties of both rotational modulation and solar-like oscillations. The code is similar to that described in Gaulme & Guzik (2019) to look for stellar pulsators A63, page 4 of 18 Fig. 3.…”
Section: A Dedicated Pipeline To Analyze the Samplementioning
confidence: 99%
“…These requirements make the Kepler space telescope an excellent instrument to study the pulsational properties of the γ Dor variables, with its very high precision and continuous data spanning over 4 years. Using Kepler data, more than 100 eclipsing binaries with a γ Dor component were discovered so far (Gaulme & Guzik 2019). Ibanoglu et al (2018) compiled a comprehensive catalogue of γ Dor variables and showed that the pulsation periods of binary γ Dor variables are proportional to their orbital periods and pulsation constants (Q), but inversely proportional to the fractional radii of the pulsating components.…”
Section: Introductionmentioning
confidence: 99%